Cloning of a gene encoding cold-adapted alpha-Amylase from the psychrotrophic bacterium Pseudoalteromonas haloplanctis strain 505 - Truong, Le Van; Hai, Truong Nam; Binh, Le Tran; Schweder, Thomas (Academia Journal of Biology, 2015)
Cloning of a gene encoding cold-adapted alpha-Amylase from the psychrotrophic bacterium Pseudoalteromonas haloplanctis strain 505